Key Concepts in Philosophy An Introduction - Ferber, Rafael (Academia Press, 2015)
The book provides an introduction to six fundamental philosophy concepts - philosophy, language, knowledge, truth, being and good. At the same time, it aims to initiate its readers into the process of philosophical thinking. The book is addressed to students and laypeople, but also contains new ideas for specialists. It is written in a clear, accessible and engaging style, and its author "shares, and manages to convey, something of Plato's own commitment to philosophy" (Phronesis).